An enhanced S-band brillouin/erbium fiber laser with an additional EDFA in sub-loop - Ahmad, Harith; San, Cheng Xiau; Harun, Sulaiman Wadi (2005)
An enhanced short wavelength band brillouin erbium fiber laser (S-band BEFL) is demonstrated using an additional erbium-doped fiber amplifier (EDFA) in the sub-loop of the laser system. Compared with the conventional BEFL without the EDFA, the enhanced BEFL has improved the number of channels as well as the tuning range which are determined by the re-injected signal power. The incorporation of the EDFA also reduces the power difference between the first Stokes and the second Stokes from 17.2 dB in conventional BEFL to 3.8 dB in the proposed BEFL. A stable output laser comb with 8 channels was obtained with Brillouin pump of 5 mW and signal at 1502 nm. The BEFL has the potential to be used in the future dense wavelength division multiplexing communication system.